Kinematic Analysis of the Stable Platform of the S-RPS-SPS Parallel Mechanism - Li Mingliang; She Shigang; Yu Zhuqing (Jixie chuandong)
Considering the fact that ships at sea will be affected by waves, sea breeze and air currents, which usually results in serious interference of equipment that needs to work in a stable environment, such as lifting platforms, radar signal capture, etc. In response to the above problems, the S-RPS-SPS parallel mechanism is established to stabilize the platform. It can realize the roll angle of the rotation around the X axis and the pitch angle of rotation around the Y axis; it can also indirectly eliminate the rotation of the hull on these two axes. Model this parallel mechanism in Solidworks software and verify the degrees of freedom. The relation between the length of two driving rods and the pose angle of the moving platform is calculated by the method of inverse pose solution. Two sets of data are obtained by inputting different angles in the range of the rotating angle of the moving platform and the expansion length of the driving rod. The calculation formula, rotation angle range and coordinates are simulated by algorithms in Matlab software, and the correctness of the moving platform pose is verified. The simulation results show that the accuracy and reliability of this mechanism in terms of kinematics are well guaranteed.